Pengaruh Kepemimpinan dan Motivasi Terhadap Kinerja Karyawan di CV. Goyang Karawang KJA Cirata - Zidan Maulana Hermawan (PT Maju Malaqbi Makkarana, 2023)
The purpose of this study was to determine the effect of leadership on employee performance at CV. Goyang Karawang KJA Cirata, to determine the effect of motivation on employee performance at CV employees. Goyang Karawang KJA Cirata and knowing the influence of Leadership and Motivation on Employee Performance at CV. Goyang Karawang KJA Cirata. The samples in this study were employees of CV. Goyang Karawang KJA Cirata totaling 56 people. This research was conducted by collecting data using a questionnaire data collection technique, then testing the data with multiple linear regression analysis. The results of this study indicate that there is no influence of leadership on employee performance at CV employees. Goyang Karawang KJA Cirata. There is an influence of motivation on employee performance at CV Employees. Goyang Karawang KJA Cirata. There is an influence of leadership and motivation on employee performance at CV Employees. Goyang Karawang KJA Cirata